The Emergence of Multi-drug-resistant and Extensively-drug-resistant Pseudomonas aeruginosa After the COVID‑19 Pandemic in North Iran - Fatemeh Hosseinzadeh; Golnar Rahimzadeh; Fatemeh Ahangarkani; Seyedeh Mahsa Salehpour; Shaghayegh Rezai; Reza Valadan; Laleh Vahedi; Somayeh Sheidaei; Faezeh Sadat Movahedi; Raha Rezai; Mohammad Sadegh Rezai (Journal of Pediatrics Review)
Background: During the COVID-19 pandemic, the excessive use of antibiotics to manage co-infections and reduce mortality rates may have contributed to the increase in antimicrobial resistance. Objectives: This research was conducted to evaluate the antibiotic resistance patterns of multidrug-resistant (MDR) Pseudomonas aeruginosa strains during the COVID-19 pandemic in North Iran. Methods: This cross-sectional research was conducted at four teaching hospitals in Sari, Iran between May 2022 and June 2023. The macro dilution broth technique was employed to determine the minimum inhibitory concentration (MIC). All isolates were screened using the multiplex polymerase chain reaction (PCR) method for blaAmpC, blaCTX, blaSHV, blaSIM, blaSPM, blaIMP, and also virulence genes, including TOXA and ExoS. Results: The antibiotics co-amoxiclav and gentamicin showed the least activity in terms of MIC50 values, while meropenem exhibited the most potent activity based on the geometric mean of minimum inhibitory concentration (GM MIC) values. The multiplex PCR method revealed that all isolates possessed the ExoS toxin gene, while the ExoA gene was not detected. The observed frequencies of resistance genes were blaSHV (91.3%), blaCTX-M (76%), blaAmpC (91.3%), and blaIMP (95.2%). The blaSPM and blaSIM genes were not distinguished. Conclusions: This research recommends piperacillin/tazobactam and meropenem for the treatment of multi-drug-resistant P. aeruginosa infections.